2022
DOI: 10.3390/polym14204323
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release Nitrogen Fertilizers with Biodegradable Poly(3-hydroxybutyrate) Coating: Their Effect on the Growth of Maize and the Dynamics of N Release in Soil

Abstract: Fertilizers play an essential role in agriculture due to the rising food demand. However, high input fertilizer concentration and the non-controlled leaching of nutrients cause an unwanted increase in reactive, unassimilated nitrogen and induce environmental pollution. This paper investigates the preparation and properties of slow-release fertilizer with fully biodegradable poly(3-hydroxybutyrate) coating that releases nitrogen gradually and is not a pollutant for soil. Nitrogen fertilizer (calcium ammonium ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…2019). However, in agreement with the present finding where the biodegradable microplastic PHB did not significantly influence total shoot biomass of plant communities ( Figure 2d ), a previous study did not find significant adverse effect of PHB on growth of Zea mays (maize) (Kontárová et al . 2022).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2019). However, in agreement with the present finding where the biodegradable microplastic PHB did not significantly influence total shoot biomass of plant communities ( Figure 2d ), a previous study did not find significant adverse effect of PHB on growth of Zea mays (maize) (Kontárová et al . 2022).…”
Section: Discussionsupporting
confidence: 94%
“…The present finding that PBS significantly suppressed plant community productivity (Figure 2a) contrasts with that of another study that found that PBS did not have adverse effects on the growth of Brassica rapa (Chinese cabbage) (Wang et al 2019). However, in agreement with the present finding where the biodegradable microplastic PHB did not significantly influence total shoot biomass of plant communities (Figure 2d), a previous study did not find significant adverse effect of PHB on growth of Zea mays (maize) (Kontárová et al 2022). In contrast to the present findings of non-significant effects of non-biodegradable microplastics PET and PVC on the plant communities (Figure 2h & i), other studies found inhibitory effects of PET on Lepidium sativum (garden cress) (Pignattelli et al 2021) and PVC on Triticum aestivum (wheat) (Xinyue et al 2021).…”
Section: Discussionsupporting
confidence: 64%
“…The abundance of chlorophyll is directly impacted by the amount of nitrogen present in plant tissues . The slow release of urea from the developed PDXE MGs, and the direct use of pure urea were compared to explain the impact of N on chlorophyll content . To investigate the effect of developed formulation, we measured the proportion of chlorophyll in maize leaves grown in the soil treated with bare urea, Urea@PDXE MGs, and pure water as a control.…”
Section: Resultsmentioning
confidence: 99%
“…58 The slow release of urea from the developed PDXE MGs, and the direct use of pure urea were compared to explain the impact of N on chlorophyll content. 59 To investigate the effect of developed formulation, we measured the proportion of chlorophyll in maize leaves grown in the soil treated with bare urea, Urea@PDXE MGs, and pure water as a control. Our results suggested that the application of Urea@PDXE MGs (90 ± 0.7 mg/g) improved the amount of chlorophyll in maize leaves (Table 4, Figure S7), which can be ascribed to the correlation between chlorophyll synthesis and the amount of nitrogen in the leaves.…”
Section: Pdxe Mgs For Slowmentioning
confidence: 99%